Preparation and Scintigraphic Evaluation of Carbon-11-Labeled 2-N-Phenethylaminoalkanenitriles - Winstead, M. B.; Podlesny, E.J., Jr; Winchell, H.S. (Nuklearmedizin - NuclearMedicine, 1978)
11C-labeled HCN was collected in water containing carrier NaCN following bombardment of 99% N2%1%H2 with 22 MeV protons. Nine 11C-labeled 2-N-phenethylaminoalkanenitrile hydrochlorides were prepared by reacting the respective aldehyde-sodium bisulfite addition adduct with phenethylamine and Na11CN containing carrier cyanide at 10–40°C for 20–25 min with subseqent extraction with ether, drying, and addition of hydrogen chloride. Similarly, “C-labeled 2-N-benzylaminobutanenitrile hydrochloride was prepared from benzylamine. Total synthesis time was 51–66 min and 6–35 mCi of product was obtained. The 11C compounds dissolved in 1–7 ml of water, dimethylsulfoxide (DMSO), or aqueous DMSO were administered intravenously to dogs, and in-vivo distribution was serially imaged scintigraphically. Following intravenous administration, 11C activity rapidly accumulated in highly perfused organs such as brain followed by rapid wash-out and redistribution of a homogeneous level of activty through most of the tissues of the body. Such a distribution is consistent with the hypothesis that these agents rapidly pass across cell membranes including the „blood-brain barrier” and equilibrate throughout both the extracellular and intracellular spaces. Dissociation of these aminonitriles occurred in vivo liberating H11CN which was partially expired in the breath. No significant renal or biliary excretion of activity was observed.